Pengawasan Bahan Baku dan Mutu yang Efektif Guna Mendukung Kelancaran Proses Produksi Pada PT Alove Bali - PRABHANINGRUM, ANAK AGUNG SAGUNG DESSY ANESTESIA; SUAMBA, I KETUT; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.1, Januari 2016, 2016)
Abstract Raw Material Control and Quality Control Effective to Support The Smooth Production Process at PT Alove Bali PT Alove Bali is one of the aloe vera  organic liquid fertilizer manufacturer in Bali. The development of  business competition makes PT Alove  Bali is more strict in achieving the aim of creating and retaining customers. To achieve this objective, PT Alove Bali must be able to produce qualified products in accordance with the needs and desires of consumers. This study aimed to analyze the raw materials and quality control of the organics liquid fertilizer on PT Alove Bali. The analysis was performed by processing the data of defective products of the organic liquid fertilizer using statistical process control (SPC) methods to p-control, cause-effect diagrams, and analyze the optimum total cost over quality . Based on this research, the companies prefer to conduct the inventory in the process , because it does not cause too big storage costs as if the companies do supply raw materials . Analysis of the quality control using the p-control, indicating that the organic liquid fertilizer is in a state of uncontrolled, since there are points that outside the control limit. Based on the analysis of cause-effect diagrams, there are four factors that cause damage to the organic liquid fertilizer that are raw materials, tools and machines, processes, and workforce . Based on analysis of the total cost of optimum quality, the optimum amount of tolerable damage are 89.715 liters, so the  total cost of optimum quality the company that should be done as much as Rp 1.327.489.411,39. Keywords : liquid fertilizer, raw material, quality control, total quality cost, cause effect diagram